Nanoscale distribution of Ge in Cu-rich sphalerite - Fougerouse, Denis; Cugerone, A.; Reddy, Steven; Luo, K.; Motto-Ros, V. (2023)
A large proportion of the critical elements resources Ge, Ga, and In are associated with sphalerite in Pb-Zn ore deposits. Germanium in sphalerite has been proposed to be structurally bound in the crystal lattice. Using a combination of microstructural, geochemical and nanoscale observations, we show that Ge can be hosted in sphalerite crystal structure as well as nanoparticles of briartite (Cu2(Zn,Fe)GeS4). The structurally-bound Ge was preserved in undeformed sphalerite grains from the Saint-Salvy Pb-Zn vein deposit (France), whereas the briartite nanoparticles were observed in metamorphosed sphalerite from Arre. The briartite nanoparticles likely exsolved from sphalerite during the Pyrenean-Alpine metamorphism and deformation. The presence of nanoparticles may harden the sphalerite during crystal-plastic deformation and help to preserve the critical elements resources of Pb-Zn deposits during metamorphism.